1996
DOI: 10.1111/j.1471-6712.1996.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Violation of the Patient's Integrity, Seen by Staff in Long‐Term Care

Abstract: The aim of the study was to describe the views held by staff (n = 233) in long-term care on what they regard as a violation of patient's integrity and to define the concept "integrity" in simple terms. The design of the investigation was inductive. The answers were coded into 775 items. Agreement was reached between the authors on 770 of the items when sorted into 13 categories: the unique personality, autonomous self, personal opinions, secret self, personal competence, professional self, family self, cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 4 publications
1
62
0
Order By: Relevance
“…Moreover, their personal competence concerning their lives and their body was questioned and they were not seriously listened to. This is also reported by Kihlgren and Thorsén [19], Randers and Mattiasson [20] and Randers et al [25] who stress that patients' integrity is threatened when their own knowledge and personal competence concerning illness and its treatment are ignored. According to Sö derberg et al [26] and Werner et al [9], health-care professionals are responsible to prevent these disempowerments, so that patients can deal with the effects of the illness instead of struggling to uphold their dignity.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, their personal competence concerning their lives and their body was questioned and they were not seriously listened to. This is also reported by Kihlgren and Thorsén [19], Randers and Mattiasson [20] and Randers et al [25] who stress that patients' integrity is threatened when their own knowledge and personal competence concerning illness and its treatment are ignored. According to Sö derberg et al [26] and Werner et al [9], health-care professionals are responsible to prevent these disempowerments, so that patients can deal with the effects of the illness instead of struggling to uphold their dignity.…”
Section: Discussionmentioning
confidence: 51%
“…Patient integrity is experienced as threatened when caregivers ignore or neglect the patients' own knowledge and personal competence concerning their disease and illness as well as the treatment of the disease [19,20]. In her study of women with fibromyalgia, Malterud [21] stressed that women's descriptions of symptoms are more often interpreted by the physicians as psychosocial problems.…”
Section: Experiences Of Care Situations When Dignity Was Not Fully Upmentioning
confidence: 99%
“…Analysing and interpreting the interviews using a phenomenological hermeneutic approach without co‐assessment is a delicate matter. I have tried to be as thorough as possible in the analyses, but it must be taken into account that different findings may have been reported by another researcher (Kihlgren & Thorsén 1996). Ricoeur (1976) holds the opinion that an interpretation is only one of several possible ones, but the findings in this study convey the most useful understanding that I have reached.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…All interviews were analysed by the first author, and five randomly selected interviews were analysed independently by the second author (M.K.). After completing the analyses, the authors found that they had not found the same themes 18,19 . The second author was then given more information about the first author’s themes, worked through the material once more, and after discussion agreed to use the themes and the presentation of them.…”
Section: Methodsmentioning
confidence: 99%